Dealing with environmental issues: preparing a framework for environmental education, policy and laws in Malaysia - Mohamad, Nor Asiah (International Islamic University Malaysia, 2007)
Much has been said about the environment, nevertheless, much of the action has yet to be seen to materialize. Even, endeavours currently in implementation do not seem to promise any good results. Yet, all seem to agree that mankind is the main cause of the destruction and losses. Man comes and goes. The present laws and policies never caveat any progress or improvement. It is mooted in this paper that what is needed for the future is simply education. A good educational system will ensure that each individual, layman or professional, goes through the same process of receiving information and knowledge. In this paper, it is submitted that Islam lays a good foundation for teaching and learning about the environment. Man-made laws alone are insufficient to create consistent awareness and consciousness as far as a duty to take good care of the environment is concerned. Natures is a great gift from the Creator for mankind, yet, they never make any effort to realize this. Thus, the foundation must fix its pillars to the belief that protecting the environment is an act of faith.